2007
DOI: 10.1158/0008-5472.can-06-2616
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-Independent Growth and Tumorigenesis of Prostate Cancer Cells Are Enhanced by the Presence of PKA-Differentiated Neuroendocrine Cells

Abstract: The neuroendocrine status of prostatic adenocarcinomas is considered a prognostic indicator for development of aggressive, androgen-independent disease. Neuroendocrine-like cells are thought to function by providing growth and survival signals to surrounding tumor cells, particularly following androgen ablation therapy. To test this hypothesis directly, LNCaP cells were engineered to inducibly express a constitutively activated form of the cyclic AMP-dependent protein kinase A catalytic subunit (caPKA), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
59
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 41 publications
15
59
0
Order By: Relevance
“…Coupling with G-proteins, it activates a number of ligand-receptor signaling pathways and controls cell growth and differentiation (Stork and Schmitt, 2002;Tasken and Aandahl, 2004). In PC, several reports have suggested its involvement with androgen-independent growth and neuroendocrine differentiation (Cox et al, 2000;Deeble et al, 2007), as well as with the cross-talk between the PKA and AR pathways in PCs (Sadar, 1999;Stork and Schmitt, 2002). The PKA pathway is regulated by many factors, including PKA-regulatory subunits (PKA-Rs) and endogenous PKA inhibitors (Miller, 2002;Taylor et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Coupling with G-proteins, it activates a number of ligand-receptor signaling pathways and controls cell growth and differentiation (Stork and Schmitt, 2002;Tasken and Aandahl, 2004). In PC, several reports have suggested its involvement with androgen-independent growth and neuroendocrine differentiation (Cox et al, 2000;Deeble et al, 2007), as well as with the cross-talk between the PKA and AR pathways in PCs (Sadar, 1999;Stork and Schmitt, 2002). The PKA pathway is regulated by many factors, including PKA-regulatory subunits (PKA-Rs) and endogenous PKA inhibitors (Miller, 2002;Taylor et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence has been presented showing that NE tumor cells can promote androgen-independent growth and tumorigenesis, 6 and invasion and metastasis of prostate cancer cells, 7 likely through their secreted products. 8,9 Studies over the years have shown that NE cells secret biogenic amines, neuropeptides and cytokines, while the bulk, non-NE tumor cells express receptors for many of the NE cell products.…”
Section: Neuroendocrine Cells In Benign Prostatementioning
confidence: 99%
“…It was further shown that NE cancer cells secrete growth stimulating peptides (e.g. bombesin) inducing increased proliferation of adjacent PCa cells [86,[88][89][90][91][92][93]. However, in small cell PCa cells, upregulation of mitotic genes (UBE2C, AURKA) and the proliferation-associated polo-like kinase 1 (PLK1) co-expressed with NE markers was identified [86] [94,95].…”
Section: Discussionmentioning
confidence: 99%
“…By identifying an additive effect of SRRM4 and AR pathway inhibition to induce NEPC, the researchers proposed a role for ADT as prerequisite condition to release a lineage-specific differentiation program and preparing transformation to NEPC [89]. The placental gene PEG10 was identified as driver of NEPC in a dynamic progression xenograft model revealing a biphasic expression pattern during distinct stages of NEPC development [90]. PEG10 expression increased during enzalutamide-mediated AR inhibition in the initial progression phase.…”
Section: Neuroendocrine Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation